Transformation from below in Bolivia and Bangladesh: Decentralization, local governance, and systemic change - Jean-Paul Faguet (London School of Economics and Political Science (LSE), Department of International Development, 2015)
I examine decentralization through the lens of the local dynamics it unleashed in the much-noted case of Bolivia and the less-noted case of Bangladesh. I argue that the national effects of decentralization are largely the sum of its local-level effects. Hence to understand decentralization we must first understand how local government works. This implies analysing not only decentralization, but also democracy, from the bottom up. Beginning with Bolivia, I explore the deep economic and institutional determinants of government quality in two extremes of municipal performance. From this I derive a model of local government responsiveness as the product of political openness and substantive competition. The quality of politics, in turn, emerges endogenously as a joint product of the lobbying and political engagement of local firms/interests, and the organizational density and ability of civil society. The model explains the micro-foundations of good vs. bad local government performance, and hence of Bolivia's overall decentralization success. I then test these ideas using qualitative data from Bangladesh. The evidence shows that civic organizations worked with NGOs and local governments to effect transformative change from the grass-roots upwards - not just to public budgets and outputs, but to the underlying behaviours and ideas that underpin social development. In the aggregate, these effects were powerful. Key development indicators show Bangladesh leap-frogging past much wealthier India between 1990 and 2015. The combination of tests shows that the model generalizes to very different institutional, cultural, and economic contexts.
Keywords: 330; democracy; decentralization; local government; good governance; civil society; Bolivia; Bangladesh